2005
DOI: 10.1007/s10162-005-0013-8
|View full text |Cite
|
Sign up to set email alerts
|

Immortalized Mouse Inner Ear Cell Lines Demonstrate a Role for Chemokines in Promoting the Growth of Developing Statoacoustic Ganglion Neurons

Abstract: The target-derived factors necessary for promoting initial outgrowth from the statoacoustic ganglion (SAG) to the inner ear have not been fully characterized. In the present study, conditioned medium from embryonic Immortomouse inner ear cell lines that maintain many characteristics of developing inner ear sensory epithelia were screened for neurite-promoting activity. Conditioned medium found to be positive for promoting SAG neurite outgrowth and neuronal survival was then tested for the presence of chemokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 28 publications
2
44
0
Order By: Relevance
“…Subsequent in vitro experiments in the developing mouse and chick, as well as analysis of Mif knockout (KO) mice, demonstrated that MIF can account for the major functional activities of ODF, including promoting SAG neuron survival and directional neurite outgrowth, and is required for normal hearing and inner ear innervation patterning. We also demonstrate that residual bioactivity in chick or mouse otocyst-generated ODF that is not removed by function-blocking antibodies to MIF can be entirely eliminated by function-blocking antibodies to the cytokine MCP1, which we previously identified as a component of ODF (Bianchi et al, 2005). Together, these data and our studies of zebrafish otic development (Holmes et al, 2011;Shen et al, 2012) show that the cytokines MIF and MCP1 (Bianchi et al, 2005) play crucial roles in inner ear development, directly demonstrating another important connection between the immune and nervous systems.…”
Section: Introductionsupporting
confidence: 51%
See 4 more Smart Citations
“…Subsequent in vitro experiments in the developing mouse and chick, as well as analysis of Mif knockout (KO) mice, demonstrated that MIF can account for the major functional activities of ODF, including promoting SAG neuron survival and directional neurite outgrowth, and is required for normal hearing and inner ear innervation patterning. We also demonstrate that residual bioactivity in chick or mouse otocyst-generated ODF that is not removed by function-blocking antibodies to MIF can be entirely eliminated by function-blocking antibodies to the cytokine MCP1, which we previously identified as a component of ODF (Bianchi et al, 2005). Together, these data and our studies of zebrafish otic development (Holmes et al, 2011;Shen et al, 2012) show that the cytokines MIF and MCP1 (Bianchi et al, 2005) play crucial roles in inner ear development, directly demonstrating another important connection between the immune and nervous systems.…”
Section: Introductionsupporting
confidence: 51%
“…Our laboratories have been investigating proteins that regulate innervation during the earliest stages of inner ear development (reviewed by Barald and Kelley, 2004;Gerlach et al, 2000), and our recent work highlights the importance of chemokines and cytokines in the early stage peripheral auditory system (Bianchi et al, 2005;Holmes et al, 2011;Shen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations